Hot and Fast BBQ on your Traeger Grill : A Pitmasters Secrets on Doubling the Flavor in Half the Time - Randolph, Ed; Randolph, Noelle (Salem, Massachusetts : Page Street Publishing Co., 2022)
"Juicy, Tender BBQ From the Grill to the Table in Record Time Award-winning pitmasters Ed and Noelle Randolph have perfected the hot and fast technique so you can spend less time grill-side while still turning out tender, fall-off- the-bone masterpieces. Hot and fast grilling means higher temperatures, shorter cooking times and the same great smoky, slow-cooked flavors you crave. Pack some heat with Competition-Style St. Louis Ribs, and then prepare a meal fit for a king with a Bourbon-Kissed Steak au Poivre. Char up some Crispy Chicken Wings with Blackberry Sauce, or try out a smoky Chile-Coffee Rubbed Tomahawk. And if you want appetizers to impress, then look no further than Ed and Noelles Lamb Lollipops with Mint Butter and Tri-Tip Crostini with Pimento Cheese. With bigger flavors and less time, this guide will transform any Traeger amateur into a pitmaster faster than you can say "barbecue.""--
Keywords: Recipes; Cookbooks